Current status of aspiration thrombectomy for acute stroke patients in China: data from ANGEL-ACT Registry. (April 2021) - Tong, Xu; Wang, Yilong; Bauer, Clayton T.; Jia, Baixue; Zhang, Xuelei; Huo, Xiaochuan; Luo, Gang; Wang, Anxin; Ma, Ning; Gao, Feng; Mo, Dapeng; Song, Ligang; et al.
Background and Aims: Although noninferior to stent retriever (SR) as first-line approach for endovascular treatment (EVT) of acute large vessel occlusion (LVO) stroke, little is known about the current status of direct aspiration (DA) as first-line thrombectomy in China. This analysis of a prospective, nationwide registry (ANGEL-ACT) aimed to investigate the prevalence and comparative effectiveness of DA-first thrombectomy in a real-world practice in China. Methods: All patients receiving thrombectomy were screened from a prospective cohort of LVO patients undergoing EVT at 111 hospitals in China between November 2017 and March 2019, and divided into two groups based upon which type of thrombectomy was attempted first ("DA-first" and "SR-first"). The following outcome measures were compared using logistic regression models with adjustment: successful recanalization after first-device alone and all procedures, use of rescue treatment, intracranial hemorrhage (ICH) within 24 h, and modified Rankin Scale (mRS) score at 90 days. Results: A total of 1225 patients, 102 (8.3%) in DA-first group and 1123 (91.7%) in SR-first group, were included. Patients receiving DA-first had less often successful recanalization after first-device alone [30.4 versus 66.4%; odds ratio (OR) = 0.23, 95% confidence interval (CI) = 0.15–0.37], more frequent rescue treatment (62.8 versus 27.0%; OR = 4.55, 95% CI = 2.92–7.08) and ICH (35.4 versus 22.1%; OR = 1.78, 95% CI = 1.12–2.83) than those receiving SR-first; however, no significant difference was found in successful recanalization after all procedures (84.3 versus 90.3%; p  = 0.18) and 90-day mRS (median: 3 versus 3 points; p  = 0.90) between both groups. Conclusion: This real-world registry suggested that DA-first thrombectomy for acute stroke patients lagged behind in China during the study period. Far fewer DA-first than SR-first thrombectomies were performed, and DA-first was associated with lower first-device recanalization, more frequently requiring rescue treatment, and increased ICH risk. Clinical Trial Registration: ClinicalTrials.gov, NCT03370939.